The use of computer guided implant surgery in oral rehabilitation: A literature review - Mascarenhas, Vinicius Ibiapina [UNESP]; de Molon, Rafael Scaf [UNESP]; Tavares, Lívia Jacovassi [UNESP]; Mendes, Lara Maria Ferreira; Tonetto, Mateus Rodrigues [UNESP]; Bandeca, Matheus Coelho (Jaypee Brothers Medical Publishing, 2014)
The virtual planning of dental implants is a technology that brings many benefits to practitioners and patients who undergo a prosthetic rehabilitation. The cone beam computed tomography (CBCT) produces high-resolution images allowing to implant a breakthrough in preoperative planning, making planning more accurate. The virtually guided surgery is a surgery planned based computers in a 3D anatomical model of the patient and transferred to the surgical procedure through guides built especially for this purpose. The objective of this study is to report the current concepts in the literature on virtually guided surgery, emphasizing its applicability, indications and benefits in prosthetic rehabilitation with dental implants. Thus, it was concluded that the technique of guided surgery represents an advance in the field of implantology significantly decreasing errors, bringing good results postoperative and increasing predictability of the results, one technique suitable for various cases.
Keywords: Dental implant; Dental prostheses; Image guided surgery